Socio-affective factors and their impact on the meaningful learning of reading and writing of students in Higher Basic Education - Ortega Manjarrez, Verónica Alexandra (2023)
The objective of this research was to analyze the socio-affective factors that intervene in the significant learning of literacy in young people in basic general education. The research has been developed following the guidelines of a quantitative study, the research method used was deductive, with a quantitative approach. The techniques used were the survey and the non-probabilistic sampling technique, whose population consisted of 12 teachers and 61 parents. The survey and questionnaire were the data collection technique and instrument respectively. The validation of the instruments was achieved through expertjudgment. The data analysis was given through the statistical software SPSS Version 25. As results have been obtained through the survey directed to teachers, it can be indicated that the socio-affective factors are correct to increase academic performance, improve positive reactions, reduce negative impulses and promote the social skills of the students, determinants in the meaningful learning of reading and writing. Regarding the survey of parents, it has been determined that the majority agree with their children’s literacy, which represents a low frequency. It is concluded that regarding the socio-affective factors that intervene in the significant learning of literacy in students of Higher Basic Education, the following have been identified: motivation, self-esteem, social skills and personality.